Kepemimpinan Kyai: Strategi Dakwah Melalui Seni Wayang di Pondok Pesantren Nurul Huda Sragen - Sriyanto Sriyanto; Zuhriana Widya; Hanifah Hikmawati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This article focuses on kyai leadership in developing da'wah strategies through wayang art at the Pondok Pesantren Nurul Huda, Sragen. This da'wah strategy refers to the da'wah pattern echoed by the Wali Songo in the past when spreading Islam without abandoning the customs, traditions and culture that had developed in the archipelago. The strategy implemented by Wali Songo is also carried out by the Pondok Pesantren Nurul Huda in Sragen, with activities that have become the pondok pesantren routine since 1986 until now, gaining enthusiasm and interest from the santri, the surrounding community and even from outside the area. This routine takes the form of recitation and wayang art which is regularly held every night of Ahad Legi.